Quality comparison of direct digital panoramic radiography and computed radiography panoramic - Dariush Goodarzipour (Journal of Oral Health and Oral Epidemiology, 2013)
BACKGROUND AND AIM: Digital panoramic X-ray images can be captured using photostimulable phosphors or solid-state detectors (i.e. charge-coupled devices and Flat-Panels). The first category is defined as computed radiography (CR) or semi-direct radiography. The second technology that uses solid-state detectors is known as direct digital radiography (DDR). Both of these technologies have their own advantages and disadvantages. One of the most important fields in comparison of these systems is their resultant image quality. The purpose of this study was to compare the subjective image quality of DDR and CR digital panoramic system, and to assess the overall density and contrast of their images.